Recent progress in the production and application of biochar and its composite in environmental biodegradation - Foong, Shin Ying; Cheong, Kah Yein; Kong, Sieng Huat; Yiin, Chung Loong; Peter Nai Yuh, Yek; Rizwan, Safdar; Liew, Rock keey; Loh, Soh Kheang; Lam, Su Shiung (Elsevier B.V., 2023)
Over the past few decades, extensive research has been conducted to develop cost-effective and high-quality biochar for environmental biodegradation purposes. Pyrolysis has emerged as a promising method for recovering biochar from biomass and waste materials. This study provides an overview of the current state-of-the-art biochar production technology, including the advancements and biochar applications in organic pollutants remediation, particularly wastewater treatment. Substantial progress has been made in biochar production through advanced thermochemical technologies. Moreover, the review underscores the importance of understanding the kinetics of pollutant degradation using biochar to maximize its synergies for potential environmental biodegradation. Finally, the study identifies the technological gaps and outlines future research advancements in biochar production and its applications for environmental biodegradation.